A Comparsion Between Landmark Identification On 2D Frontal Radiograph and3D rendered volumesFrom CBCT Scans - Hasan, Abdulkarim (Latakia University Journal -Medical Sciences Series, 2018)
The cone-beam computed tomography(CBCT) provided the chance to the practitioners to generate three dimensions volumes using personal computer’s programs . The quick spread of this available technology will doubtless widens the 3d imaging in orthodontics. It is not clear whether these volumes give the similar amount of accuracy when compared to the two-dimensional projections of thesame scanning. The aim of this research is to investigate the differences between the measurements on the reconstructed size of the CBCTScans and the traditional method of determining measurements on two-dimensional images in the measurements taken on the frontal image. Under the circumstances of this research, there was a statistical difference in one variable out of three variables included in the research مقارنة بين تحديد النقاط المرجعية على الصورة الجبهية ثنائية البعد والحجم ثلاثي الأبعاد المأخوذين من المسح الطبقي المحوسب المخروطي أعطت تقنية المسح الطبقي المحوسب المخروطي للممارسين السريرين الفرصة لتوليد حجوم ثلاثية الأبعاد باستخدام برامج حاسوبية شخصية. انتشار هذه التكنولوجيا المتاحة بسرعة سيوسع بلا شك استخدام التصوير الشعاعي ثلاثي الأبعاد في مجال تقويم الأسنان.من غير الواضح إن كانت هذه الحجوم تعطي المقدار المشابه من الدقة عند مقارنتها بالمساقط ثنائية البعد لنفس المسح. هدف هذا البحث هو تقصي وجود فروق بين إجراء القياسات على الحجم المعاد بناؤه من المسح الطبقي المحوسب المخروطي والطريقة التقليدية في تحديد القياسات على الصور ثنائية البعد وذلك في القياسات المأخوذة على الصورة الجبهية. ضمن ظروف هذا البحث كان هناك فرق إحصائي عند متغير واحد من أصل ثلاث متغيرات شملها البحث.